Sleep problems in four-year-old children: The significance of children’s temperament, mothers’ parenting strategies and sleep regime - Baukienė, Edita; Jusienė, Roma (Psichologija, 2016)
Children’s sleep problems are widely investigated, but questions about the longitudinal effects of child’s temperament and parenting strategies as well as sleep hygiene and regime in preschool age still remain not clearly answered. This study aimed to analyse whether and how a four-year-old’s sleep problems relate to children’s temperament traits and mothers’ coping with children’s negative emotions, as well as whether sleep problems could be explained by children’s sleep regime assessed one year ago. Data about 162 children collected during the outgoing longitudinal study on early development of self-regulation were used in this study. Mothers reported their strategies on Coping with Children’s Negative Emotions Scale – CCNES (Fabes, Eisenberg, Bernzweig, 1990), answered questions about child’s sleep regime, and evaluated child’s temperament with Children’s Behaviour Questionnaire Short Form (Rothbart, Ahadi, Hershey, & Fisher, 2001) when children were 3-year-old. The children’s sleep problems were assessed using the Child Behaviour Checklist (CBCL/1½-5) at age four-year-old. Results showed a positive relationship between children’s sleep problems and negative emotionality. The sleeping place (e.g., sleeping with parents or separately) was not found as a significant factor, however, the regularity of sleep/wake time (stable sleep regime) was revealed as important. Pre-schoolers who had no regular sleeping regime at age three had higher sleep problem scores after one year. Negative emotionality related to sleep problems. Results of regression analysis revealed that neither regular sleep/wake regime, nor negative emotionality significantly predicted sleep problems. Finally, regular sleep/wake regime was not revealed as a mediator between the negative emotionality and sleep problems in pre-school age. On the one hand, these results suggest that the importance of temperament for the sleep problems could be less provident in pre-school age than in infancy. On the other hand, the pattern as well as reasons for sleep problems could change dramatically in pre-school age. Thus, developmental interactions of sleep problems, sleep regime, parenting behaviours and child’s temperament – especially reactivity and regulation – should be further studied more comprehensively.